Non-pecuniary damages for human rights violations, 2003-2016 - Fikfak, Veronika (UK Data Service, 2021)
When individuals are mistreated by European governments, the European Court of Human Rights is responsible for reviewing state actions under the European Convention of Human Rights. If the individuals are successful in proving a violation, the ECtHR may award them damages for the treatment suffered. The dataset contains the non-pecuniary damage amounts for each victim of human rights violations in three types of cases that the ECtHR has decided from 2003 to 2016: cases of torture, inhuman and degrading treatment (article 3), cases of arbitrary detention (Article 5) and cases of violations of the right to life (article 2). The dataset contains details of what happened in each case (which violations the Court recognised), as well as characteristics of each of the victims (gender, age etc). All three files together, contain information about 3169 victims of human rights violations, along with the details of the legal qualifications of state conduct against these victims. When individuals are mistreated by European governments, the European Court of Human Rights is responsible for reviewing state actions under the European Convention of Human Rights. If the individuals are successful in proving a violation, the ECtHR may award them damages for the treatment suffered. Whilst domestic courts of the 47 Council of Europe (COE) Member States, over which the Court has jurisdiction, usually award damages on the basis of scales that are public, this is not the case with the ECtHR. The Court sets out no rules or guidelines as to when individuals are likely to get compensation; it also does not explain which elements of their treatment applicants should emphasise nor how much they should ask for. There is no information about maximum or minimum amounts awarded to individuals for specific violations nor about how claims in one case might compare to those in other cases. Often, individuals turning to the Court ask for millions of euros in damages, but only receive a few thousand. Many scholars insist that in the human rights context damages can play a crucial role in ensuring individual justice. The process of according compensation focuses the proceedings before the court on the individual, the victim of the violation and allows him/her the vindication of their rights. But the current practice of the Court appears arbitrary and opaque. In response to demands from practice (lawyers who represent victims of rights violations and national judges who enforce judgments of the Court), this project seeks to fill the gap created by the ECtHR practice for the first time. Through an empirical quantitative and qualitative study of the last ten years of caselaw relating to just satisfaction, the project will discern the legal principles from the practice of the Court and critically assess the Court's role in awarding compensation for human rights violations. It does this in three steps: First, the project quantitatively analyses thousands of cases of the ECtHR to determine when and how the Court awards damages for human rights violations. Second, the project looks at the legal basis on which the Court exercises its function. As an international court, the ECtHR only has subsidiary jurisdiction to award damages. National courts are arguably better placed to adapt compensation to the specific jurisdiction or the facts of the case. Thus, when the Court decides to award damages, it faces important questions of legitimacy. Through interviews with judges the project therefore seeks to understand how those who sit on the Court perceive its role in protecting human rights. Building on both stages, the final step of the project examines the discrepancies between how the ECtHR judges perceive human rights and what monetary value they attach to them. In dialogue with judges, causes and justifications for these discrepancies will be identified and possible solutions explored. The project brings together academics and practitioners from different jurisdictions of the COE to fill the gap created by the Court. Through research visits to the Court, advisory group meetings and a three-day dissemination workshop, practitioners, government officials, and national and European judges will be consulted to ensure cross-fertilisation and knowledge exchange. They will be involved in the preparation, implementation as well as dissemination of the project so as to guarantee the greatest impact. This project can make a fundamental contribution to human rights law by creating a new law of human rights damages. It will generate an important amount of new data, which will be empirically analysed for the first time to seek out legal principles to be applied in future cases both on the international level and in courts of the 47 countries of the COE. More broadly, the project represents an exciting opportunity to explain better the role of the ECtHR and understand what drives its practice of compensating for human rights violations.